Constitutional and Jurisdictional Review of Natural Resource - Eddy, Triono (CV. Inara, 2022)
The constitution mandates that natural resources should be used as much as possible to improve the welfare and prosperity of the people, but in practice they are over-exploited and their utilization is controlled in part by national and foreign investors/investors for business purposes. This research was conducted to determine the constitutional basis and juridical basis of natural resource management. This research is a normative research. The type of normative legal research is a series of activities carried out with the aim of getting a reference to a problem taken by using legal materials as an indicator. The constitutional basis for managing the environment and natural resources of Indonesia is the Preamble to Paragraph IV of the 1945 Constitution of the Republic of Indonesia.